Eksistensi Lembaga Adat Desa Sebagai Alternatif Penyelesaian Konflik Sosial di Masyarakat Kabupaten Lombok Barat - Fathony Karuniawan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Traditional village institutions are an important part of the social structure of the people of West Lombok Regency. This study aims to analyze their existence as an alternative for resolving social conflicts based on local wisdom. Using a qualitative approach and descriptive method, data were obtained through in-depth interviews, observation, and documentation studies with customary leaders, village officials, and community members. The results show that traditional village institutions still have a strong existence. The conflict resolution mechanism is carried out through customary deliberation that prioritizes the principles of kinship, consensus, restorative justice, and the restoration of social relationships between conflicting parties. The success of traditional institutions is supported by the social legitimacy of customary leaders, cultural proximity to the community, and flexibility in adapting conflict resolution to the local context. However, traditional village institutions face challenges such as social changes in society, declining compliance with customary norms, and limited formal recognition within the state legal system. Therefore, adaptation strategies and institutional strengthening are needed to keep traditional village institutions relevant and sustainable as an alternative for resolving social conflicts in society